Measuring the economic impact of environmental sustainability practices: a systematic literature review - Balsiūnaitė, Rimantė; Petrusevičienė, Irma; Lekavičius, Vidas (Transformations In Business & Economics, 2026)
This study examines methodological approaches used to evaluate the economic impacts of environmental sustainability practices. The research is based on a systematic literature review conducted using the SALSA framework and the PRISMA statement to ensure transparency and reproducibility. After implementing the PRISMA statement for the articles found, 62 articles were identified. In addition, the snowball method was employed, and 13 more articles were discovered. The analysis shows that the most frequently discussed practices in the reviewed literature relate to renewable energy consumption (50 percent of studies analyzed), waste management (6.6 percent), environmental taxation (6.6 percent), and the circular economy (6.6 percent). However, some practices emphasized in the global sustainability agenda, such as energy efficiency and green finance, receive comparatively limited attention in the literature. In addition, there is a noticeable lack of studies comparing these practices. The most applied methods include econometric analyses (64.6 percent of studies analyzed), which typically examine relationships among variables; economy-wide assessments such as computable general equilibrium (CGE) models (9.8 percent); and product-specific evaluations, including life cycle costing (LCC) (8.5 percent), and life cycle assessment (LCA) (8.5 percent). Econometric methods are particularly valued for their ability to establish statistical relationships and test causality, while LCC and LCA provide comprehensive insights into environmental and economic performance across the life cycle of a product or process. CGE models, in turn, offer an economy-wide perspective by capturing intersectoral linkages and feedback effects. This article also discusses the definition of environmental sustainability practices and identifies several methodological gaps, including the limited use of holistic econometric assessments, the need for integrated methodological approaches that combine multiple methods, and the insufficient evaluation and comparison of sustainability practices addressing global environmental challenges.